Crop diversification pattern in Haryana: A comparative study of organic and inorganic farmers - Satish Kumar; Mahabir Singh Jaglan (National Geographical Journal of India, 2022)
The adoption of organic farming helps increase agriculture's profitability, enhancing food's nutritional value and sustaining the health of soils, ecosystems, and people. It has become popular in Haryana during the recent period. The present study analyzes the salient features of the adoption process of organic farming, and its impact on cropping patterns, crop combinations, and diversification. It is a primary data-based comparative study of organic and inorganic farmers of the state. The data has been collected from 234 farm households with the help of a structured questionnaire. The study analyses the main factors in the adoption of organic farming in the state. The comparisons of cropping patterns, crop combination, and crop diversification have been done by applying statistical techniques such as Doi method, and Herfindahl Index. The study reveals that farmers with small land holdings but higher education levels prefer organic farming. Though organic farming is carried out at a small scale in the state, it has been pursued earnestly as about half of the organic farmers devote more than three-fourths of their land to this form of farming. Organic farmers grow a larger number of crops and have quite a diversified cropping pattern compared to inorganic farmers. There is a perceptible difference in this regard in organic farming across agro-eco regions. The lesser irrigated mixed-crop region has much more diversified than the wheat-rice region of the eastern parts of the state.